INFLUENCE AUDIT TENURE, AUDITORS SWITCHING, FINANCIAL DISTRESS, AND COMPANY SIZE ON THE AUDIT REPORT LAG IN MINING SECTOR COMPANIES REGISTERED IN EXCHANGE EFFECT INDONESIA PERIOD 2018-2021 - Jochelyn Chu; Triana; Ys.Wandi Lahagu; Teng Sauh Hwee; Wenny Anggeresia Ginting (ZILLZELL MEDIA PRIMA, 2024)
This research aims to identify the effect of audit tenure, auditor switching, financial distress, and company size on audit report lag. The method applied in this research is a quantitative method by processing secondary data which is collectedthrough the official website of IDX. The population includes all the mining companies listed on the Indonesia StockExchange (IDX), with a total of 48 companies in 2018-2021. Then, by using a purposive sampling technique to determine the sample, 42 companies were taken as samples with 129 observations data over a period of 4 years. In order to realize the purpose of this research, SPSS application was used to analyze data with multiple linear regression analysis technique. Simultaneous tests resulted that audit tenure, auditor switching, financial distress, and company size together have a significant effect on audit report lag. Meanwhile, the results of partial tests are only financial distress that has a negative and significant effect on audit report lag, while audit tenure has no effect on audit report lag. US well as auditor switching and company size.